A syndrome of severe intellectual disability, hypotonia, failure to thrive, dysmorphism, and thinning of corpus callosum maps to chromosome 7q21.13‐q21.3. Issue 2 (5th May 2022) - Halperin, Daniel; Agam, Nadav; Hallak, Maher; Feinstein, Miora; Drabkin, Max; Yogev, Yuval; Wormser, Ohad; Shavit, Eitan; Gradstein, Libe; Shelef, Ilan; Mijalovsky, Aanalia; Flusser, Hagit; et al.
Abstract: Six individuals of consanguineous Bedouin kindred presented at infancy with an autosomal recessive syndrome of severe global developmental delay, positive pyramidal signs, unique dysmorphism, skeletal abnormalities, and severe failure to thrive with normal birth weights. Patients had a profound intellectual disability and cognitive impairment with almost no acquired developmental milestones by 12 months. Early‐onset axial hypotonia evolved with progressive muscle weakness, reduced muscle tone, and hyporeflexia. Craniofacial dysmorphism consisted of a triangular face with a prominent forehead and midface hypoplasia. Magnetic resonance imaging (MRI) demonstrated thinning of the corpus callosum and paucity of white matter. Genome‐wide linkage analysis identified a single ~4 Mbp disease‐associated locus on chromosome 7q21.13‐q21.3 (LOD score>5). Whole‐exome and genome sequencing identified no nonsynonymous pathogenic biallelic variants in any of the genes within this locus. Following the exclusion of partially resembling syndromes, we now describe a novel autosomal recessive syndrome mapped to a ~4Mbp locus on chromosome 7. Abstract : We describe a novel autosomal recessive syndrome mapped to a ~4Mbp locus on chromosome 7; Six individuals of consanguineous kindred presented at infancy with a severe global developmental delay, positive pyramidal signs, unique dysmorphism and failure to thrive, with MRI demonstrating thinning of the corpus callosum and white matter paucity.